Legal Practice Experience for an Engaged Scholarship: A call for access to advocate’s license for Ethiopian law schools’ instructors - Beyene, Temesgen Sisay (Bahir Dar University Journal of Law, 2022)
Theoretical and practical experience of law instructors is very essential to handle practice- oriented and clinical courses in law schools. Unless theory is integrated with practical experience, quality education may be compromised. This article explores the relationship between legal practical experience of law instructors and quality legal education in law schools. In doing so, the writer examined the legal regime in Ethiopia that regulates the licensing and registration of advocates to practice law in Ethiopian courts vis-à-vis the curriculum of law schools and proves that there is no law that permits law instructors to access advocates’ licenses. Moreover, it examined the experiences of selected countries. The findings of this article revealed that, the delivery of clinical and practice-oriented courses in Ethiopian law schools were managed by instructors with no practical legal experience, and quality of instruction is compromised. To ensure quality education through an engaged scholarship, access to advocate’s license for law instructors needs an immediate response and the law should be revised to pave the way for law instructors to deliver an engaged scholarship in their career.